Epigenetic Diet to Modulate Immune Response against SARS-CoV-2 - Andika, Andika; Ahdyani, Risa; Erlina, Linda; Azminah, Azminah; Yanuar, Arry (Pharmaceutical Sciences and Research, 2020)
The COVID-19 pandemic has spread to various parts of the world and caused many deaths. The victims are infected by SARS-CoV-2, a new type of coronavirus that has appeared since December 2019 and caused respiratory symptoms, fever, coughing, and shortness of breath. In addition to social distancing, wearing masks and washing hands, diet is important as a defense of the body against SARS-CoV-2. In this review, researchers conducted epigenetic diet studies that could potentially inhibit SARS-CoV-2, and can be consumed and used on a daily basis.